(untitled) (Circe de clásicos y modernos, 2022)
The purpose of this article is to analyze Philo’s presentation of the Exodus and the Conquest of Canaan in the historical section of the apologetic treatise Hypothetica (5. 11-7. 20), and the motivations that could have guided this representation. We will inquire other narratives of these same episodes to which Philo can be responding, and we will try to demonstrate that the oddness and novelty of the treatise among Philo’s works can be explained from its production in the changing and urgent context of the Jewish-Alexandrian conflicts of the years 38-40, but they should not hide the lines of continuity between this text and other Philonic writings.